Development and economic policy in the UAR (Egypt) - Hansen, Bent.; Marzouk, Girgis A. (Amsterdam : North-Holland Pub. Co., 1965)
This book is an economic analysis written by economists. In this volume the author have tried to draw a picture of the economic development and the economic policies pursued in Egypt-The United Arab Republic since 1959-during the post-war period. General surveys in foreign languages of the Egyptian economy do exist, but they have mostly the character of economic-historical records of events, general descriptions of the structure of the Egyptian economy, or superficial journalism, in any case containing little of economic analysis proper.
Includes bibliographical references and Index.
hza 21/06/2018
Loans
Keywords: Economic policy; Egypt